2014
DOI: 10.1038/ncomms6045
|View full text |Cite
|
Sign up to set email alerts
|

Soft epitaxy of nanocrystal superlattices

Abstract: Epitaxial heterostructures with precise registry between crystal layers play a key role in electronics and optoelectronics. In a close analogy, performance of nanocrystal (NC) based devices depends on the perfection of interfaces formed between NC layers. Here we systematically study the epitaxial growth of NC layers for the first time to enable the fabrication of coherent NC layers. NC epitaxy reveals an exceptional strain tolerance. It follows a universal island size scaling behaviour and shows a strain-driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 31 publications
(43 reference statements)
0
54
0
1
Order By: Relevance
“…Two main factors that control the polymer chain orientation on CNTs during crystal growth are epitaxy and geometrical confinement. When the radius of gyration of a polymer is comparable to CNTs diameter, the polymer chains are forced to align to the CNT's long axis, regardless of the CNTs chirality . In PE‐b‐PEG, PE is the portion of the copolymer that plays the main role because its radius of gyration is comparable with CNTs diameter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two main factors that control the polymer chain orientation on CNTs during crystal growth are epitaxy and geometrical confinement. When the radius of gyration of a polymer is comparable to CNTs diameter, the polymer chains are forced to align to the CNT's long axis, regardless of the CNTs chirality . In PE‐b‐PEG, PE is the portion of the copolymer that plays the main role because its radius of gyration is comparable with CNTs diameter.…”
Section: Resultsmentioning
confidence: 99%
“…The prefix number for each segment represents for their weight percentage (Table ). In our previous work, we found that values of the NHSK parameters (diameter, thickness, and periodicity) are the functions of crystallization time, so we selected crystallization time as 1 hour and 6 hours. The results are presented in the preceding sections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6B) (82,83). Using the principle of epitaxy, nanoparticle superlattices of one type can even be used as a template for the growth of subsequent nanoparticle crystals of a different type (75). To realize the full potential of this approach, it would be advantageous to develop high-throughput printing techniques that could define nanoscale features into microscale patterns over millimeter lengths.…”
Section: From Nanoparticles To Colloidal Crystalsmentioning
confidence: 99%
“…Criterion 2: Orientation. The vast majority of nanoparticle assemblies reported use spherical building blocks that, as a result of their continuous rotational symmetry, can adopt any orientation in a crystal and remain equivalent (57,62,(73)(74)(75). The use of anisotropic nanoparticles as building blocks breaks this symmetry and generates inequivalent particle orientations (Fig.…”
Section: From Nanoparticles To Colloidal Crystalsmentioning
confidence: 99%